The effects of psychological skills training for a canoe athlete - Park, Y.-j.; Hwang, J. (Korean Journal of Sport Science, 2020)
The purpose of this studied to improve athletes` performance through sports psychological skills training and counseling of a male canoe player in high school. Methods: One male high school athlete in J area was interviewed for sports psychological skills training and counseling, and interviewed athletes and coaches diagnosed the potential psychological problems of athletes. Through this process, the athlete gained the ability to control anxiety about the game and strengthened the attention-focused ability to increase his confidence and set a goal for improving concentration. For effective training, sports psychological counselors, athletes, and coaches met once a week to create a routine. and participated in direct training on a boat with the coach every week. Sports psychological skills, anxiety about competition, and self-management of athletes were measured before and after to confirm the effectiveness of training of athletes' psychological skills. Results: As a result, athletes' psychological skills and anxiety decreased, their confidence increased, and their concentration, which was diagnosed as an urgent problem of athletes, improved. Conclusions: psychological skills of athletes, psychological shortcomings of players were reinforced, thus enhancing the athletes' performance. This suggests the effectiveness and necessity of training in sports psychological skills. It is hoped that continued support will serve as an opportunity to diagnose potential psychological problems of student athletes and apply them to training to contribute to improving their performance.